Development of HTML5-Based Mobile Learning Media to Enhance Critical Thinking Skills of Elementary School Students in IPAS Learning - Himmah, Elok Faiqotul; Astutik, Sri; Aristya, Pramudy Dwi (Universitas Pendidikan Mandalika, 2024)
This study aims to examine the validity, practicality, and effectiveness of HTML5-based mobile learning media to enhance the critical thinking skills of elementary school students in science learning (IPAS). The research method used was Research and Development (R&D) with the ADDIE model (analysis, design, development, implementation, evaluation). The study subjects were fourth-grade elementary students from two schools, SDN Yosowilangun Kidul 01 and SDN Yosowilangun Kidul 03 in Lumajang Regency. Data collection techniques included questionnaires, expert validation instruments, practicality instruments, and pretest-posttest data. Data analysis was conducted using a descriptive quantitative approach, focusing on student needs and the validity, practicality, and effectiveness of HTML5-based mobile learning media. The results showed that the HTML5-based mobile learning media had an average validity score of 88.9%, categorized as